The evolution of the spatial and sectoral patterns in Ile-de-France over 1978-1997 - Rachel Guillain; Julie Le Gallo; Céline Boiteux-Orain (European Regional Science Association (ERSA), 2004)
The aim of this paper is to analyze the intra-urban spatial distribution of employment in the agglomeration of Ile-de-France in 1978 and 1997. In that purpose, exploratory spatial data analysis is used in order to identify employment centers and a sectoral analysis of the CBD and the subcenters is performed. Our results highlight a suburbanization process of employment between 1978 and 1997 in Ile-de-France. A more polarized space emerges in 1997 compared to 1978 with several employment centers specialized in different activities. Moreover, even if the spatial influence of the CBD is diminishing during the study period, the CBD preserves its economic leadership by concentrating a large variety of high-order producer services. Keywords: exploratory spatial data analysis; employment centers; spatial autocorrelation; suburbanization JEL Classification: C12, R12, R14
Keywords: C12; R12; R14; 330; exploratory spatial data analysis; employment centers; spatial autocorrelation; suburbanization